Empowering Primary School Teachers: The Vital Role of Mother Tongue as a Medium of Instruction - Verma, Rachana (THE PRIMARY TEACHER, 2025)
The language that a person first learns, typically from their parents or other caregivers, is referred to as their mother tongue. The purpose of this review paper is to investigate the significance of mother tongue language as a teaching method for primary school teachers in India. The purpose of the study is to analyse the challenges and opportunities faced by teachers and students in using mother tongue as the medium of instruction. The review analyses relevant literature published from 2000 to 2023 to gather evidence and identify the strengths and limitations of using mother tongue as the medium of instruction. The findings suggest that using mother tongue as the medium of instruction positively impacts the teaching and learning process, helps students to develop better language proficiency, and enhances their cognitive abilities. However, the study also identifies some limitations in the implementation of mother tongue as the medium of instruction, such as a lack of trained teachers, limited resources, and the need to integrate mother tongue with other languages in the curriculum. The paper concludes by summarising the main points and providing suggestions for future research.